Fecal Calprotectin as a Selection Tool for Small Bowel Capsule Endoscopy in Suspected Crohn's Disease. Issue 9 (2nd May 2018) - Monteiro, Sara; Barbosa, Mara; Cúrdia Gonçalves, Tiago; Boal Carvalho, Pedro; Moreira, Maria João; Rosa, Bruno; Cotter, José
Abstract: Background: Small bowel capsule endoscopy (SBCE) is a firstline examination in patients with suspected Crohn's disease (CD) after negative ileocolonoscopy. Fecal calprotectin (FC) is a noninvasive marker of intestinal inflammation. The aim of this study was to evaluate the predictive value of FC in inflammatory activity detected by SBCE in patients with suspected CD. Methods: This is a retrospective study including patients who underwent SBCE for suspected CD between March 2015 and October 2016. FC was measured within 1 week of SBCE. Inflammatory activity at SBCE was considered significant when the Lewis score (LS) was ≥135. FC correlation with LS was assessed using the Spearman correlation. The diagnostic accuracy of FC for significant inflammatory activity at SBCE was calculated by the area under the receiver operating characteristic curve (AUC). Results: Seventy-five patients were included: 52 females (69.3%), with a mean age of 37 years. SBCE detected significant inflammatory activity (LS ≥ 135) in 42 patients (56%), and FC was positively correlated to LS (rank correlation = 0.56; P < 0.001). The AUC of FC was 0.854 for significant inflammatory activity (LS ≥ 135). For values of FC ≥100 µg/g, an LS ≥135 was found in 33 of 37 patients (89.2%, P < 0.001), corresponding to a sensitivity, specificity, positive predictive value, and negative predictive value of 78.6%, 87.9%, 89.2%, and 76.3%, respectively. Conclusions: FC has shown a good ability to predict significant inflammatory activity in SBCE in patients with suspected CD. Thus, FC proved to be a useful tool to select patients with suspected CD for SBCE.